Scientology and Sex: The Second Dynamic, Prenatal Engrams, and the Sea Org - Cusack, Carole M. (Nova religio, 2016)
While the control and discipline of the body and human behavior is a perennial concern in all social orders, it is particularly acute within religions, both old and new. Religions typically regulate dress, social interaction, diet, and especially norms concerning sex, reproduction, and the family. To date, research on the Church of Scientology, founded by L. Ron Hubbard in 1954, has neglected the topic of sex. In this article, I remedy this lacuna by examining three areas linked by the theme of “attempted abortion.” First, I explore Hubbard’s biography in terms of sexual and familial experiences; second, I expound on his writings about sex and the doctrinal position of the Church of Scientology; and third, I examine recent allegations affecting the Sea Org due to defectors’ claims that pregnant women were forced to have abortions. Additionally, I adduce some comparative material from the biography of Sun Myung Moon, founder of the Unification Church, who manifested a similar disconnect between his personal life and his conservative teachings on sex. In the Church of Scientology, sexual orientation and activity are prime sites of control experienced by all its members, but in particular among the elite corps of the Sea Org.